Assessment of the bioremediation technique in the attenuation of an oil from the Campos Basin/RJ - Alves, Alexsandro da Silva (2021)
Various types of operations with petroleum are carried out in the Campos Basin/RJ, which results in risks of environmental accidents as a result of a spill and / or contamination of the environment with oil. The aim of this research is to evaluate the use of the bioremediation technique in the attenuation of an oil from this region. The bioremediation of an oil from the Campos Basin by microrganisms present in local sea water was simulated in laboratory in units containing NPK fertilizer with components of the saturated and aromatic fractions of the oil. After seven days, the effect of the bioremediation on the aromatic and saturated fractions of the oil was assessed by means Gas Chromatography / Mass Spectrometry (GC / MS). When compared to a reference simulation, that did not use an exogenous stimulant, one can conclude that the NPK fertilizer does have a positive effect of stimulation. Aromatic compounds had a negative influence on the biodegradation of saturated compounds due to their complexity, toxicity and stability.